Tuning lipid accumulation and fitness of motile algae via hydrodynamic cues - Kakavand, Narges; Sengupta, Anupam (Frontiers in Bioengineering and Biotechnology, 2026)
Achieving enhanced lipid yield without compromising biomass is a central challenge for sustainable algal biofuel production. While temperature, nutrients, and light can induce lipid accumulation, they often reduce overall fitness, offsetting net gains. By contrast, hydrodynamic cues remain underexplored, particularly in the context of motile algae and their physiological response in terms of fitness and lipid production. Here, we investigate Heterosigma akashiwo, a well-known motile phytoplankton species, exposed to controlled hydrodynamic cues at two physiological stages: immediately after inoculation (lag phase) and during the mid-exponential growth phase. We quantify intracellular lipid accumulation, growth kinetics, and photophysiology, and compare these parameters between two different strains of H. akashiwo. Early induction of hydrodynamic cues (during the lag phase) increased average cytoplasmic lipid accumulation by nearly 300% at the single-cell level, without adverse effects on fitness and biomass production. Growth rate accelerated while photophysiological performance was preserved. In contrast, delayed induction (exponential phase) yielded only marginal lipid enhancement and reduced biomass and photosynthetic efficiency. At the strain level, these trends were consistent, while we note strain-specific differences in the extent of the response. These results identify the onset timing of hydrodynamic cues as a tunable parameter to enhance lipogenesis while preserving physiological fitness, suggesting a simple and potentially scalable route to improve lipid production using motile microalgae.